Set-up and instrumentation of the greenhouse gas measurements on experimental sites of continuous cover forestry - Laurila, Tuomas; Aurela, Mika; Hatakka, Juha; Hotanen, Juha-Pekka; Jauhiainen, Jyrki; Korkiakoski, Mika; Korpela, Leila; Koskinen, Markku; Laiho, Raija; Lehtonen, Aleksi; Leppä, Kersti; Linkosalmi, Maiju; et al. (Natural Resources Institute Finland (Luke), 2021)
A set of experimental study sites was established to monitor greenhouse gas (GHG) emissions from drained peatland forests under different harvesting regimes in Finland. The purpose of these experimental sites is to study the effects of continuous cover forestry (CCF) and clear-cutting (CC) on ecosystem processes including GHG emissions and stand development on drained peatland forests. The sites represent fertile Norway spruce dominated peatland forests, where soil GHG emissions are high due to drainage that has exposed peat to decomposition in aerobic conditions. Two “flagship” sites for greenhouse gas (GHG) monitoring have been established and instrumented by the Natural Resources Institute Finland (Luke), University of Helsinki (UH) and the Finnish Meteorological Institute (FMI). The sites host continuous GHG monitoring with Eddy Covariance (EC) towers and with automatic chambers. In addition, greenhouse gas (CO2, CH4, and N2O) emissions are monitored with manually operated chambers at four sites, where effects of selection (CCF) harvests are studied with replicated treatments. These data will be used to calculate the ecosystem and soil GHG balances of the sites by using methodologies standardized earlier and compatible with the IPCC guidelines. On all experimental sites, ground water table (WT), tree growth and regeneration are monitored in different management trials. These data will form the basic data needed for designing and demonstrating optimal harvesting cycles and evaluating and generalizing the climate impacts. The results including the biological drainage capacity (evapotranspiration) of different-sized tree stands as well as the soil GHG balance of different tree stand – WT combinations will be incorporated into existing models that can be used to estimate the mitigation obtained with different management options and in different site and climatic conditions. The study sites are actively used for training and demonstration of alternative peatland management practices by host projects and by multiple stakeholders. The host projects and organizations also promote further extensions for the measurements and all complementary research activities are welcome to these study sites.
Keywords: climate change; continuous cover forestry (CCF); drained peatland forest; ecosystem study; eddy covariance; greenhouse gas (GHG); managed peatland; water quality; water table